Trends in self-reported arterial hypertension in Brazilian adults: an analysis of data from the Brazilian National Household Sample Survey, 1998-2008 Tendência temporal de hipertensão arterial autorreferida em adultos: uma análise da Pesquisa Nacional por Amostra de Domicílios, 1998-2008 - Ludmila Correa Muniz; Andreia Morales Cascaes; Fernando César Wehrmeister; Jeovany Martínez-Mesa; Aluisio J. D. Barros; Ana Maria Baptista Menezes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This study investigated the time trend in self-reported arterial hypertension from 1998 to 2008 in individuals older than 20 years in Brazil. Data were analyzed on prevalence of hypertension from the National Household Sample Survey (PNAD) for the years 1998, 2003, and 2008. The analysis considered the sampling complexity and included 203,419, 238,591, and 257,816 individuals in the years 1998, 2003, and 2008, respectively. The time trend in hypertension was analyzed by sex, family income, geographic regions of Brazil, and area of residence (urban versus rural), and the prevalence rates were adjusted for age. Prevalence of self-reported hypertension was 12.5% in 1998, 13% in 2003, and 13.9% in 2008, with an annual increase of 1.07%. The highest increases occurred in the Southeast Region (1.41%), in men (1.82%), and in urban areas (1.15%). The study showed a rise in the prevalence of self-reported hypertension in all income brackets and with increasing age. Knowledge of the prevalence of hypertension is essential for backing activities to prevent and control the problem, especially among the more vulnerable subgroups. O estudo avaliou a tendência temporal de hipertensão arterial autorreferida no período de 1998 a 2008, em indivíduos acima de 20 anos, no Brasil. Foram analisados os dados de prevalência de hipertensão da Pesquisa Nacional por Amostra de Domicílios (PNAD) de 1998, 2003 e 2008. A análise considerou a complexidade amostral e incluiu 203.419, 238.591 e 257.816 indivíduos nos anos de 1998, 2003 e 2008, respectivamente. A tendência de hipertensão foi descrita por sexo, renda domiciliar, macrorregiões do Brasil e zona de residência, e as prevalências foram ajustadas por idade. A prevalência de hipertensão foi de 12,5% em 1998, 13% em 2003 e 13,9% em 2008, com incremento anual de 1,07%. Maior aumento anual ocorreu na Região Sudeste (1,41%), entre homens (1,82%) e na zona urbana (1,15%). Observou-se crescimento nas prevalências de hipertensão em todos os quintis de renda e conforme aumento da idade. Conhecer a abrangência da hipertensão é fundamental para subsidiar ações preventivas e de controle para o problema, sobretudo entre os subgrupos mais expostos.